2023
DOI: 10.1002/ijc.34663
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide study of genetic polymorphisms predictive for outcome from first‐line oxaliplatin‐based chemotherapy in colorectal cancer patients

Abstract: We conducted the first large genome‐wide association study to identify novel genetic variants that predict better (or poorer) prognosis in colorectal cancer patients receiving standard first‐line oxaliplatin‐based chemotherapy vs chemotherapy without oxaliplatin. We used data from two phase III trials, NCCTG N0147 and NCCTG N9741 and a population‐based patient cohort, DACHS. Multivariable Cox proportional hazards models were employed, including an interaction term between each SNP and type of treatment for ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have illuminated various genetic variations associated with the therapeutic effectiveness in CRC, offering insights into potential genetic biomarkers relevant to CRC treatment. These include therapies targeting epithelial growth factor receptor (EGFR) [ 9 , 10 ], immunotherapies [ 11 ], and chemotherapy regimens involving agents such as 5-FU [ 12 , 13 , 14 , 15 ] and oxaliplatin [ 16 , 17 , 18 , 19 ]. Notably, a comprehensive genome-wide association study (GWAS) has revealed single nucleotide polymorphism (SNP) biomarkers that may predict the clinical outcomes of both intermediate and advanced CRC patients undergoing oxaliplatin-based adjuvant chemotherapy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have illuminated various genetic variations associated with the therapeutic effectiveness in CRC, offering insights into potential genetic biomarkers relevant to CRC treatment. These include therapies targeting epithelial growth factor receptor (EGFR) [ 9 , 10 ], immunotherapies [ 11 ], and chemotherapy regimens involving agents such as 5-FU [ 12 , 13 , 14 , 15 ] and oxaliplatin [ 16 , 17 , 18 , 19 ]. Notably, a comprehensive genome-wide association study (GWAS) has revealed single nucleotide polymorphism (SNP) biomarkers that may predict the clinical outcomes of both intermediate and advanced CRC patients undergoing oxaliplatin-based adjuvant chemotherapy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include therapies targeting epithelial growth factor receptor (EGFR) [ 9 , 10 ], immunotherapies [ 11 ], and chemotherapy regimens involving agents such as 5-FU [ 12 , 13 , 14 , 15 ] and oxaliplatin [ 16 , 17 , 18 , 19 ]. Notably, a comprehensive genome-wide association study (GWAS) has revealed single nucleotide polymorphism (SNP) biomarkers that may predict the clinical outcomes of both intermediate and advanced CRC patients undergoing oxaliplatin-based adjuvant chemotherapy [ 19 ]. However, a comprehensive study, especially in the context of a GWAS, investigating 5-FU-based adjuvant therapy, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%